A nurse's step-by-step guide to transitioning to an academic role : strategies to jumpstart your career in education and research - Mumba, Mercy Ngosa, 1987- (Sigma, 2022)
"Starting any new professional endeavor can be as challenging and overwhelming as it is exciting. Moving from practice to education can further amplify the uncertainty. Academia is a whole different world, which means a unique new culture, different priorities, and a complete change in your day-to-day work life. Lucky for your soon-to-be students, you already know what it takes to be a strong, competent clinician. You just need to transfer that knowledge to future nursing professionals. A Nurse's Step-by-Step Guide to Transitioning to an Academic Role gives you a detailed road map for a successful transition to academia. Using a conversational tone and highly practical tools, author Mercy Ngosa Mumba explains how to: Understand different types of academic appointments. connect with colleagues and students, juggle various academic responsibilities, manage your time and stress, and contribute to a more equitable institutional culture. This book will help you draw upon your strengths to create a new, successful, and satisfying academic career that supports the nursing profession. Whether in your first or second year, this book offers crucial guidance in learning how to balance competing priorities and avoid burnout. You will learn to not just survive but thrive in academia!"--